Dooby dooby moo - Cronin, Doreen; Lewin, Betsy (New York : Atheneum Books for Young Readers, 2006)
While Farmer Brown sleeps, his animals prepare for a talent show at the county fair.
003-007.
Mode of access: Internet.
Keywords: Humorous stories; Farmers -- Fiction; Domestic animals -- Fiction; Talent shows -- Fiction; Farmers -- Juvenile fiction; Domestic animals -- Juvenile fiction; Talent shows -- Juvenile fiction